Research on economic and financial socialisation in Poland and worldwide: A bibliometric analysis - Żebrowska, Julita; Lizińska, Joanna (Research Papers in Economics and Finance, 2025)
Economic and financial socialisation is essential for building a person’s confidence in managing finances independently and fostering financial self-sufficiency. The growing complexity of the financial environment, marked by market globalisation, digital transformation and accessibility of sophisticated financial products, creates unprecedented challenges for individual financial decision-making. This situation is further complicated by generational changes and challenges such as underperforming pension systems, making research on economic and financial socialisation particularly relevant and timely. The aim of this article is to review research on economic and financial socialisation, enabling a comprehensive mapping of existing studies and the identification of key topics and underexplored areas that may guide future studies. Conclusions are drawn from a quantified bibliometric analysis of articles from the Scopus database, supplemented by an in-depth content analysis of purposefully selected scientific works. The analysis was conducted using the R environment, specifically the Bibliometrix package and the Biblioshiny functionality. The findings map the status and developments of the research existing in the field, indicating also a need for further research into the impact of economic and financial socialisation on a broad spectrum of financial decision-making in adulthood.